Continuous Robust Task-Space Tracking Control of Robotic Manipulators with Uncertain Dynamics - Cetin, Kamil; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan (IEEE, 2015)
In this work, the problem of robust task space control of robotic manipulators with continuous control inputs have been considered. Under mild assumptions on kinematic formulation and dynamics of the robot manipulator, a continuous robust controller have been proposed. The proposed controller ensures asymptotic end-effector tracking despite the presence of unstructured uncertainties associated with the dynamical terms. Numerical simulations conducted on a two degree-of-freedom robot manipulator is also presented to illustrate the feasibility and performance of the proposed controller.
IEEE Conference on Control and Applications (CCA) -- SEP 21-23, 2015 -- Sydney, AUSTRALIA
Keywords: Approximate Jacobian Control; Kinematics; Matrix